Engineering of tissue inhibitor of metalloproteinases mutants as potential therapeutics. - Nagase, H; Brew, K (2002)
Matrix metalloproteinases (MMPs) play a central role in many biological processes such as development, morphogenesis and wound healing, but their unbalanced activities are implicated in numerous disease processes such as arthritis, cancer metastasis, atherosclerosis, nephritis and fibrosis. One of the key mechanisms to control MMP activities is inhibition by endogenous inhibitors called tissue inhibitors of metalloproteinases (TIMPs). This review highlights the structures and inhibition mechanism of TIMPs, the biological activities of TIMPs, the unique properties of TIMP-3, and the altered specificity towards MMPs achieved by mutagenesis. A potential therapeutic use of TIMP variants is discussed.